Catherine's war - Billet, Julia (Harper Alley, 2020)
Rachel Cohen is living in Sèvres Children's Home outside Paris prior to WWII when the Nazis arrive and she is forced to change her name to Catherine Colin. As she flees danger, she takes along her most precious possession, a camera, with which she documents her own survival story.